Pengaruh Pemberian Essential Oil dari Serai dan Jeruk Nipis terhadap Tekanan Darah pada Lansia dengan Hipertensi di Wilayah Kerja Puskesmas Nguter - Eka Deviany Widyawaty; Heni Nur Kusumawati (Rena Cipta Mandiri, 2026)
Background: Hypertension is one of the most common non-communicable diseases among older adults and a major risk factor for cardiovascular diseases. Complementary therapy using essential oils has the potential to help control blood pressure through relaxation and vasodilatory effects. Objective: To analyze the effect of lemongrass (Cymbopogon citratus) and lime (Citrus aurantifolia) essential oils on blood pressure among older adults with hypertension in the working area of Nguter Primary Health Center. Methods: This study employed a quasi-experimental design with a one-group pretest-posttest repeated measures approach. A total of 30 hypertensive older adults were recruited using purposive sampling. The intervention consisted of inhalation of lemongrass and lime essential oils through a diffuser for 30 minutes daily for 14 consecutive days. Blood pressure measurements were conducted at baseline, day 7, and day 14. Data were analyzed using the Friedman Test for systolic blood pressure and Repeated Measures ANOVA for diastolic blood pressure. Results: Mean systolic blood pressure decreased from 156.90±10.53 mmHg to 135.67±7.01 mmHg, while mean diastolic blood pressure decreased from 93.30±8.01 mmHg to 80.70±4.69 mmHg. Statistical analysis revealed significant effects on both systolic (p<0.001) and diastolic blood pressure (p<0.001). Conclusion: Lemongrass and lime essential oils were effective in reducing blood pressure among older adults with hypertension and may serve as a promising complementary non-pharmacological therapy.